Identifying demand for health resources using waiting times information - Richard Blundell; Frank Windmeijer (Institute for Fiscal Studies (IFS), 2000)
less skilled workers has deteriorated, either through their ability to secure jobs and/or their ability to earn a decent wage. Some have linked this decline to modern computing technologies. This paper surveys the evidence on the effects of technical change on skills, wages and employment by examining the micro-econometric evidence (we take this to include studies at the industry, firm, plant and individual levels). We focus on over 70 empirical studies that have used direct measures of technology (rather than associating technology with a residual time trend). We first point to three basic methodological problems relating to endogeneity, fixed effects and measurement. Our survey comes to the following tentative conclusions: (i) there is a strong effect of technology on skills in the cross section which appears reasonably robust to various econometric problems; (ii) there is a strong effect of diffusion of technologies on wages in the cross section which is not robust to endogeneity and fixed effects; (iii) at the firm level product innovations appear to raise employment growth, but there is no clear evidence of a robust effect (either positive or negative) of process innovations or R&D on jobs.
Keywords: 330; Gesundheitsökonomik; Großbritannien